The evaluation of an ambulance rear compartment using patient simulation: Issues of safety and efficiency during the delivery of patient care. (November 2019) - Hallihan, Greg; Caird, Jeff K.; Blanchard, Ian; Wiley, Katelyn; Martel, Jessica; Wilkins, Matt; Thorkelson, Brent; Plato, Mike; Lazarenko, Gerald
Abstract: The purpose of this study was to evaluate the safety and efficiency of a specific ambulance while providers delivered basic and advanced life support. Forty-eight, Emergency Medical Service (EMS) teams were observed delivering care to a simulated patient during an anaphylaxis scenario in a moving ambulance that contained a complete compliment of medical supplies and equipment. A detailed coding system was developed and applied to the audio and video behavioural data. Patterns of interaction among EMS personnel, the patient, equipment and the ambulance interior during the patient simulation scenario were analyzed. The results revealed a number of issues associated with the patient compartment including: potentially unsafe seated and standing positions; hazardous barriers to movement around the patient; difficulties accessing equipment and supplies; and the adequacy of work surfaces and waste disposal. A number of design recommendations are made to guide provider and patient comfort, efficiency and safety. Highlights: The safety and effectiveness of an ambulance was evaluated during basic and advanced life support to a simulated patient. Patterns of interaction among providers, patient, equipment, supplies and the ambulance interior were coded and analyzed. The safety of providers was compromised by not wearing a seatbelt and stepping over or passing under cabling and tubing. Efficiency of care was affected by a lack of usable work surfaces and convenient sharps and garbage containers. Design recommendations are made based on the results and other human factors guidelines for the patient compartment.